Value creation and capture from sustainability-oriented innovations in a shared semiconductor infrastructure - Piia Konstari; Katri Valkokari (Sustainable Technology and Entrepreneurship)
A shared semiconductor research infrastructure can be studied as a local innovation ecosystem consisting of an infrastructure-operating company and user companies. This study focuses on investigating the forms of sustainable value that such infrastructure provides for its users, as well as value creation and capture from sustainability-oriented innovation activities in a shared infrastructure. The research was conducted as a qualitative multiple-case study in a Finnish semiconductor innovation ecosystem at the end of 2023. It shows that the shared infrastructure provided users with environmental, social, and economic forms of sustainable value. The study also provides evidence that value creation from sustainability-oriented innovations takes place at three levels—operational, organizational, and system—in a shared infrastructure. The value is then captured through an increase in company value, user company business growth, and business expansion through open innovation, consumption data availability, best practice dissemination, and knowledge development, as well as new entrepreneurial opportunities by the infrastructure-operating company. This study contributes to the discussion and understanding of value creation and capture from sustainability-oriented innovations in the semiconductor industry. The results can be used by entrepreneurs, decision-makers, and management to understand how they can capture value from sustainability-oriented actions.